2009
DOI: 10.1186/1472-6831-9-28
|View full text |Cite
|
Sign up to set email alerts
|

Improved ability of biological and previous caries multimarkers to predict caries disease as revealed by multivariate PLS modelling

Abstract: BackgroundDental caries is a chronic disease with plaque bacteria, diet and saliva modifying disease activity. Here we have used the PLS method to evaluate a multiplicity of such biological variables (n = 88) for ability to predict caries in a cross-sectional (baseline caries) and prospective (2-year caries development) setting.MethodsMultivariate PLS modelling was used to associate the many biological variables with caries recorded in thirty 14-year-old children by measuring the numbers of incipient and manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Most commonly, mutans streptococci (Streptococcus mutans and Streptococcus sobrinus) and/or lactobacilli are targeted since these organisms show a positive correlation with caries. 44 It has been reported that patients with RPDs had significantly higher levels of mutans streptococci and lactobacilli than patients with fixed prostheses. 45 However, individuals with fixed prostheses had greater numbers of natural teeth than those with removable appliances.…”
Section: Mutans Streptococci and Lactobacillimentioning
confidence: 98%
“…Most commonly, mutans streptococci (Streptococcus mutans and Streptococcus sobrinus) and/or lactobacilli are targeted since these organisms show a positive correlation with caries. 44 It has been reported that patients with RPDs had significantly higher levels of mutans streptococci and lactobacilli than patients with fixed prostheses. 45 However, individuals with fixed prostheses had greater numbers of natural teeth than those with removable appliances.…”
Section: Mutans Streptococci and Lactobacillimentioning
confidence: 98%
“…Dental caries, a persistent infectious disease, affects billions of people with large individual differences in numbers of caries lesions and activity ( Selwitz et al, 2007 ; Nordlund et al, 2009 ; Kassebaum et al, 2015 ). At least half of school children and the vast majority of adults worldwide experience accordingly caries, and the economic burden of caries and dental diseases represents about 4.6% of global health expenditures ( Listl et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The participants were selected according to the following criteria: children aged between three and five years, residing in the geographical area of the target population of study, officially registered in foster homes of the region, and that parents accepted to participate in the study by signing an informed consent. The study excluded children who presented some type of physical or motor disability that would hinder their following instructions to obtain the samples of dental plaque, as well as children receiving antibiotic treatment within the three months prior to the study 14 .…”
Section: Methodsmentioning
confidence: 99%